Scientific Literacy in Islamic Schools: Harmonizing Religious Values and Scientific Knowledge - Rasyid, Muhammad; Unayah, Habibatul; Aminatun, Tien; Wantara, Ngade; Cahyati, Necta Ayu (Proceeding International Conference on Religion, Science and Education, 2025)
The integration of scientific literacy within Islamic schools presents unique challenges and opportunities as educators strive to balance religious values with modern scientific knowledge. This article explores how Islamic schools harmonize these two aspects to provide a holistic educational experience. Data from the study indicate that 75% of teachers incorporate scientific literacy into their curriculum, yet only 52% of students feel adequately instructed in science. Major challenges include reconciling scientific theories, such as evolution, with traditional Islamic teachings. To address these challenges, educators use strategies like contextual learning, where Qur'anic verses are linked with scientific principles, and inquiry-based learning, which encourages student exploration and critical thinking. Despite the benefits of these approaches, teachers face significant obstacles, including a lack of professional development and community resistance. 65% of educators report encountering opposition from parents when controversial scientific topics are taught. However, students express a desire for more hands-on experiments and real-world applications, with 68% believing that these methods would enhance their understanding of science in an Islamic context. This study highlights the need for comprehensiveteacher training and greater community engagement to successfully integrate scientific literacy while maintaining Islamic values, ensuring that students are equipped for the complexities of modern scientific challenges without compromising their faith.